Experimental and numerical study of free water exit and re-entry of a fully submerged buoyant spheroid. (July 2018) - Wu, Q.G.; Ni, B.Y.; Xue, Y.Z.; Zhang, A.M.
Highlights: Water exit and re-entry of a fully-submerged spheroid is simulated by experiment and numerical model. The breakup and reformation of the free surface are solved numerically. Liquid jet of the free surface after the body re-entering water is investigated. A local high-pressure region is generated just below the free surface under the impact of water convergence. Abstract: The entire process of free water exit and re-entry of a fully-submerged spheroid with a density slightly less than that of water is investigated by using model experiments and numerical simulations. In the experiments, an initially static body with a density slightly less than that of water was released underwater and high-speed photography was used to monitor the motion of the body and the deformation of the free surface. In addition, a numerical method is developed based on the boundary-element method for the velocity potential with fully nonlinear boundary conditions and is used to numerically analyze the free-surface breakup and reformation. Numerical results are quantitatively consistent with experimental data. The results demonstrated that an upward-oriented liquid jet, or "splash, " forms after the body fully re-enters water. It is found that this jet originates from a local high-pressure region just below the free surface that results from the impact of water quickly converging to the vacancy above the body. The local high-pressure region is transient, so the acceleration, pressure, and fluid force exerted on the body are disturbed abruptly. According to the results, initial submergence depth and density of the body are two dominant parameters. Enhancing initial submergence parameter λ or decreasing the body density ρ 1 (still larger than a critical density ρ 1, c to avoid the body exiting water totally) will induce a more severe impact of converging water after the free surface reforms, and consequently cause larger variations in the amplitude of the fluid force and of the acceleration and in the pressure on the body.